2019
DOI: 10.1590/1678-4685-gmb-2017-0314
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of naturally rare Calibrachoa species with small distribution in southern Brazil

Abstract: Calibrachoa is a South-American genus comprising 27 species, several considered endemic or rare; few were subjects in genetic studies. We attempted to generate new data about the phylogenetically related and rare species C. eglandulata, C. sendtneriana, C. serrulata, and C. spathulata concerning their genetic diversity and population structure, which, coupled with their known restricted distribution, could help access their conservation status and contribute to the study of the Brazilian biodiversity. We seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…Calibrachoa elegans presented even lower genetic diversity indices compared to other Calibrachoa species as well as P. mantiqueirensis . The four micro-endemic highland species, C. eglandulata , C. sendtneriana , C. serrulata and C. spathulata , which have population sizes and geographical ranges similar to C. elegans , possess greater genetic diversity indices for both plastid and nuclear markers (John et al 2019), whereas based on plastid diversity, the widespread species C. sellowiana (π = 0.088 %; J. N. Fregonezi et al ., unpubl. data) and C. heterophylla (π = 0.41 %; Mäder et al 2013) also have greater genetic diversity than C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Calibrachoa elegans presented even lower genetic diversity indices compared to other Calibrachoa species as well as P. mantiqueirensis . The four micro-endemic highland species, C. eglandulata , C. sendtneriana , C. serrulata and C. spathulata , which have population sizes and geographical ranges similar to C. elegans , possess greater genetic diversity indices for both plastid and nuclear markers (John et al 2019), whereas based on plastid diversity, the widespread species C. sellowiana (π = 0.088 %; J. N. Fregonezi et al ., unpubl. data) and C. heterophylla (π = 0.41 %; Mäder et al 2013) also have greater genetic diversity than C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we showed the highest component of genetic diversity of C. pygmaea is within populations based on both marker types, as seen through AMOVA results. This species possesses high genetic variability compared to other Calibrachoa species (i.e., John et al 2019), as observed by the number and haplotype diversity, as well as the nuclear marker diversity indices, despite also displaying elevated levels of inbreeding -suggested by the high and significant FIS values. Clearly dependent on pollinators, this species' genetic structure and diversity may be affected by crossings between related individuals more than gene flow between populations.…”
Section: Discussionmentioning
confidence: 85%
“…Генетически однородные популяции более подвержены влиянию биотических и абиотических факторов и могут элиминироваться в результате распространения болезней и патогенов, а популяции с более узким диапазоном генотипов могут исчезать при экстремальных климатических условиях, таких как жара, холод, засуха и т. д. [4,14].…”
Section: рис 1 электрофорез результатов пцр с использованием 2076 Ipbs-праймера для популяции ббз (дорожки 2-20)unclassified